Spirit Moderasi Beragama dalam Kisah Perjumpaan Elia dan Janda Di Sarfat - Saputra, Jefri Andri (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2025)
Inter-religious conflict is a phenomenon that still occurs in inter-religious and intra-religious relations in Indonesia. Some of the history of violence that occurred came from religious motives. Responding to this problem, the author attempts to construct a spirit of religious moderation by learning from the experience of meeting Elijah and the Widow in Zarephath. The meeting between these two figures was full of friendliness and harmony without considering their differences in background. The author analyzes this story using a literature study approach and hermeneuthic method, especially seeing through method. The author finds that the story of Elijah and the Widow at Zarephath offers three attitudes or perspectives in constructing religious moderation, namely making hospitality theology as the basis for the theology of religions, deconstructing negative stigma towards other religions through encounter and dialogue, and not exclusiveizing God's power and love.